Sucrose supplements in cattle given grass silage-based diet. 3. Rumen pool size and digestion kinetics - Huhtanen, P.; Khalili, H. (Elsevier, 1991)
In a 4 X 4 Latin square experiment, 4 male Friesian cattle with rumen and duodenal cannulae were given a basal diet of grass silage 700, barley 240 and rapeseed meal 60 g/kg total DM at the rate of 5.3 kg DM/day (diet C) or supplemented with sucrose 1.0 kg/day given twice daily (diet S), twice daily with sodium bicarbonate 0.25 kg/day (diet B) or as a continuous intraruminal infusion (diet I). Pool sizes of rumen digesta and its components, and digestion kinetics of cell wall carbohydrates, were derived from rumen evacuation. The potential digestibility of rumen digesta and faeces was estimated by incubating the samples for 240 h in nylon bags in the rumen. The main effect of sucrose supplements was to increase rumen pool size of DM and fibre constituents. The greater rumen pool size of neutral detergent fibre (NDF) and acid detergent fibre (ADF) with sucrose diets consisted mainly of digestible NDF and ADF. Inclusion of sodium bicarbonate in the diet almost completely eliminated the effect of sucrose on rumen pool size. There were close negative correlations (r2 0.96-0.999) between rumen pool size of cell wall components and in vivo digestibility of the corresponding component. Rates of digestion (kd) were decreased by sucrose supplements. Values for kd of NDF were 0.0594, 0.0444, 0.0557 and 0.0448 for diets C, S, B and I, respectively. Rate of passage (kd) or its reciprocal, rumen residence time (RRT), were not significantly affected by diet. Longer RRT was measured for digestible NDF (71.5 h) than for total NDF (61.7 h) and for indigestible NDF (49.7 h). Potential digestibility of DM, NDF and ADF of rumen ingesta and faeces was higher with diets S and I than with diets C and B. Faecal output of digestible NDF was greater with diets S and I than with diets C and B.